2018
DOI: 10.1002/dev.21738
|View full text |Cite
|
Sign up to set email alerts
|

Isolation‐induced ultrasonic vocalizations in pups: A comparison between Long‐Evans, Sprague–Dawley, and Wistar rats

Abstract: Rat pup ultrasonic vocalizations (USV) are usually studied in outbred rats belonging to either Long-Evans, Sprague-Dawley, or Wistar stocks, but these were not compared so far. We therefore performed a stock comparison and analyzed USV of male pups (postnatal day 11) belonging to these three stocks. Pups of all three stocks showed substantial isolation-induced USV, but differed in various call features, like call numbers, peak frequency, and frequency modulation. Also, three different call types were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 72 publications
5
7
0
Order By: Relevance
“…To our knowledge only two studies characterized acoustic characteristics of isolation USVs in normally reared Sprague Dawley pups into types distinguished by frequency 16,26 . In a comparative study of the three most widely used outbred strains (Wistar, Long Evans, and Sprague Dawley), Wöhr and Schwarting tested PND11 pups during a single ten minute isolation, then classified the calls into three clusters by frequency and frequency modulation 16 . Calls classified as Type 1 and 2 in their study resemble the low and high frequency calls described here, but they further classified low frequency calls (~39.6 kHz) into a third class that had large frequency modulation (called Type 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge only two studies characterized acoustic characteristics of isolation USVs in normally reared Sprague Dawley pups into types distinguished by frequency 16,26 . In a comparative study of the three most widely used outbred strains (Wistar, Long Evans, and Sprague Dawley), Wöhr and Schwarting tested PND11 pups during a single ten minute isolation, then classified the calls into three clusters by frequency and frequency modulation 16 . Calls classified as Type 1 and 2 in their study resemble the low and high frequency calls described here, but they further classified low frequency calls (~39.6 kHz) into a third class that had large frequency modulation (called Type 3).…”
Section: Discussionmentioning
confidence: 99%
“…Given that our maternal behaviour observations did not distinguish among pups within the litter, we are limited to speculating that males are more likely to reflect effects of maternal care on USVs. A recent series of studies examining strain differences between the three most common inbred rat strains found that peak frequencies and the proportion of low/high frequency isolation-induced USVs were conserved between the sexes in unrelated male and female Sprague Dawley rat pups 16,45 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern of emitting vocalizations could appear by the natural vocal selection that was demonstrated in infant rats [ 35 ]. Although there are some differences in the number of emitted calls, peak frequency, and frequency modulation among male and female pups of the main laboratory strains of Wistars, Long–Evans, and Sprague Dawley rats [ 36 , 37 ], the principle of locating the calling pup remains the same.…”
Section: Evolution and Functions Of Rat Vocalizationsmentioning
confidence: 99%
“…A very recent study that used the same poly I:C treatment (5 mg/kg on GD 15) as was used in the present study also found that poly I:C animals called less but that the call duration did not differ between treatment groups (Potasiewicz et al, 2020). Further, SD rat pups produce fewer calls and spend less time calling than Long Evans and Wistar rats (Schwarting & Wöhr, 2018). Also, in rat pups, the number of calls is more affected by the stress caused by maternal separation than other call features like call duration (Stark et al, 2020).…”
Section: Discussionsupporting
confidence: 72%